Field Deployment of Natural Gas Pipeline Pre-Warning System With CEEMDAN Denoising Method - Jun Li; Ruixu Yao (IEEE Photonics Journal, 2024)
This work utilizes the CEEMDAN algorithm to analyze the interference of Rayleigh back-scattering signals in standard communication optical fibers. The technology has several advantages, such as anti-electromagnetic interference, improved electrical insulation, corrosion resistance, higher sensitivity, and the capability for long-distance monitoring. In this study, in-situ monitoring data from a 53.2 km natural gas pipeline in a terrain area in Southwest China were analyzed. The results demonstrate that, using the CEEMDAN algorithm for a blind test conducted over fourteen days, a 100% recognition accuracy for mechanical tamping and a Nuisance Alarm Rate (NAR) of less than 1% were achieved.